KUPATAN, TRADISI UNTUK MELESTARIKAN AJARAN BERSEDEKAH, MEMPERKUAT TALI SILATURAHMI, DAN MEMULIAKAN TAMU - Wildan Rijal Amin (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2017)
The Kupatan tradition is a kind of celebrating selametan which is practiced by the Javanese people of Durenan village, Trenggalek, East Java by opening houses in order to be visited by the other villagers/guests. During the celebration, the people of Durenan prepared ketupat as its beverages for their guests on the day eight of Idl Fitr, after finishing the syawal fasting. The tradition which is coming from Mbah Mesir and followed by his grandchild, Kyai Abdul Fattah Muâ€™in, then practiced by the people of Durenan village heredity for almost 200 years. Based on the living hadith study found out that this tradition is part of the people of Durenan in practicing the Prophet Muhammadâ€™s Pbh. Teachings, which deals with the alms, strengthening people brotherhood, and glorifying the guests to make the life to be more blessed. The ancestors and Kyai have the role to contextualize text, social reality, and local people daily life, which then practiced into this selametan tradition.Â